2003
DOI: 10.1046/j.1528-1157.2003.32602.x
|View full text |Cite
|
Sign up to set email alerts
|

A Study of 43 Patients with Panayiotopoulos Syndrome, a Common and Benign Childhood Seizure Susceptibility

Abstract: Summary:Purpose: To determine prevalence, clinical, EEG features, and prognosis of Panayiotopoulos syndrome and to examine the proposition that clinical manifestations are more important than EEG findings.Methods: We analyzed retrospectively the clinical and EEG records of 1,340 children with one or more focal seizures seen in the last 18 years, supplemented with a prospective study from 1998. Panayiotopoulos syndrome was defined by clinical criteria, mainly ictal emesis, irrespective of EEG findings.Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
85
0
12

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(108 citation statements)
references
References 27 publications
11
85
0
12
Order By: Relevance
“…In a significant way, differences were not observed between the children presenting occipital or centro-temporal focal EA or normal EEG with respect to the total number of seizures, the duration or the type of seizure. These findings are consistent with the initial description of Panayiotopoulos and that of other authors 1,2,5,9 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In a significant way, differences were not observed between the children presenting occipital or centro-temporal focal EA or normal EEG with respect to the total number of seizures, the duration or the type of seizure. These findings are consistent with the initial description of Panayiotopoulos and that of other authors 1,2,5,9 .…”
Section: Discussionsupporting
confidence: 93%
“…In 29.6% of the cases, blockage or attenuation of the occipital EA was caused by opening the eyes, a lower percentage than the 80% and 100% of cases reported respectively by Caraballo et al 9 and Verroti et al 13 , but similar to that reported by other authors 5,14 .…”
Section: Discussionsupporting
confidence: 82%
“…В одном ис-следовании сообщалось о наличии связи с хромосо-мой 15 при идиопатической детской эпилепсии с центротемпоральными спайками [22], хотя в дру-гом исследовании этот локус найден не был [36]. О наличии 1 сиблинга с синдромом Панайотопулоса сообщалось в исследовании одной группы [15], и 2 пары больных сиблингов были отмечены в ка-ждом из двух других исследований [5,21]. В 1987 г. было опубликовано сообщение о наличии у 3 сиблингов затылочной эпилепсии типа Гасто, хотя описанные симптомы (в том числе дебют в возрасте 4-5 лет) полностью соответствовали синдрому Па-найотопулоса [20].…”
Section: этиология и патогенезunclassified
“…Так, иктальная рвота, в целом нетипичная для эпилепсии, при син-дроме Панайотопулоса встречается приблизительно в 80 % случаев [5,7,15,21]. При ночных приступах рвота обычно является первым и очевидным призна-ком [7].…”
Section: клиническая картинаunclassified
“…The early onset benign idiopathic occipital lobe epilepsy, presently reported as Panayiotopoulos syndrome (PS), has generated a lot of interest in recent years (Lada et al, 2003;Carabalo et al, 2007;Koutroumanidis, 2007). Despite the relatively easy recognition of clinical symptoms (Ferrie et al, 2006), the highly variable characteristics of the interictal EEG activity have prevented the determination of a consistent localization for the epileptic focus (Panayiotopoulos, 2002).…”
Section: Introductionmentioning
confidence: 99%